Direct limits of infinite-dimensional Carnot groups - Moisala, Terhi; Pasqualetto, Enrico (MATHEMATICA SCANDINAVICA, 2022)
We give a construction of direct limits in the category of complete metric scalable groups and provide sufficient conditions for the limit to be an infinite-dimensional Carnot group. We also prove a Rademacher-type theorem for such limits.